CAI [Computer-aided instruction] shell - Benemerito, Mark John G. (1995)
Through the years, the integration of the computer in the life of men has very much increased. The computer is a tool whose purpose is to lighten man's burden. This is also the case in the field of instruction. The learning process can be made easier and more convenient for both the teacher and the student with the help of the computer. Nothing can replace the teacher but supplementing the instruction which happens inside the classroom can only make things better for both parties. Computer-Aided Instruction is not new in the world today but examples of CAI in the past have only catered to a specific area or subject. Knowing this, there is a need to go further and look for a CAI tool that will be flexible such that no matter what topic, it will provide the teacher a way to present his topic with an option of checking his students have learned. This is what CAI Shell hopes to be. In order to come up with the CAI Shell, a lot of research was needed. Other computer-aided instruction packages from the past served as preliminary models for the CAI Shell. From different reading materials was discovered the strategies of Computer-Aided Instruction which could be integrated with the project. A lot of research was also put in for the Graphical User Interface, Text Editor and Graphics Editor of the CAI Shell. Designing the project was crucial because through this, possinle problems in creating CAI Shell were anticipated. After the design, the coding and testing followed. The CAI Shell is a tool through which a teacher can present a topic with text and graphics with an option to check his students comprehension through an exam. This way, the teacher can supplement his teaching inside the classroom. Through the CAI Shell, the teacher will enjoy preparing his presentations and the student will delight in viewing the lectures and exam. The CAI Shell provides security so the teacher can be secure that no unauthorized user will be able to tamper or view his files. After viewing a presentation and answering an exam, the student need not worry that his exam may be viewed by anyone outside his teacher. The CAI Shell is programmed in C. Because of this, a lot of time was spent in making the graphical user interface. Making use of windows-based languages would have enabled the group to concentrate on more difficult modules such as the sound module. Text and graphical presentations, when accompanied by sound will be more effective in providing education and learning pleasure.